Pengenalan dan Penyuluhan Tanaman Obat Tradisional untuk Diabetes Melitus pada Siswa SMK PAB-3 Medan Estate: Introduction and Counseling of Traditional Medicinal Plants for Diabetes Mellitus to SMK PAB-3 Medan Estate Students - Simarmata, Yettrie Bess Congencya; Naldi, Jefri; Ardiani, Rani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Diabetes is a disease that is a problem in the world, and Indonesia had the fifth-highest prevalence of diabetes in the world in 2021 with 19.47 million patients. One of the efforts that can be made to treat diabetes mellitus is with traditional medicine that comes from nature. The purpose of this community service activity is to increase the understanding of knowledge about diabetes mellitus and the use of traditional medicinal plants as therapy for diabetes mellitus. This community service method uses an educational method with the target being students of SMK PAB-3 Medan Estate. In the initial stage, a pretest session was conducted, followed by an education session related to the knowledge of diabetes mellitus and the utilization of traditional medicinal plants. In the final stage, a post-test was conducted. The results of this community service show that there is an increase in community knowledge before education, which is 40%, increasing after education by 60%.